Comparison of vertebroplasty using directional versus straight needle. (18th March 2015) - Soon, Wai Cheong; Mathew, Ryan K; Timothy, Jake
Background: Percutaneous vertebroplasty is a minimally invasive procedure that can be performed to treat pain and immobility associated with vertebral compression fractures. Previous studies have shown that a single injection can achieve adequate fill across the midline of the vertebral body. Purpose: To compare the radiological outcomes of using a novel steerable needle with using a conventional, straight needle in unipedicular vertebroplasty. Material and Methods: Data were collected from 19 patients who were operated at our institute between 1 September 2010 and 31 March 2011. Outcomes were measured in terms of radiological evidence of midline crossing of cement. The available pre- and postoperative pain scores and complications were reviewed. Student's t-test was used to compare mean cement projection across the midline in both groups with P < 0.05 considered to be statistically significant Results: Mean fill across the midline was significantly greater with the steerable needle (58%) compared with the straight needle (35%) ( P = 0.046). Cement leakage was higher with the steerable needle (44% versus 30%); however no clinical complications were reported in either group. Conclusion: Percutaneous vertebroplasty using a directional needle is an excellent example of advancement and refinement in spinal surgery without increased clinical risk. Our results indicate that the novel technique can potentially provide better radiological outcomes when compared with a straight needle. A larger, randomized multicenter prospective trial would be valuable in confirming these findings.